Direct costs of dementia in nursing homes - Caravau, Hilma (2018)
Dementia represents an economical burden to societies nowadays. Total dementia expenses are calculated by the sum of direct and indirect costs. Through the stages of the diseases, as the patients may require institutionalization or a formal caregiver, the direct costs tend to increase. This study aims to analyze the direct costs of dementia in Portuguese nursing homes in 2012, compare the spending between seniors with and without dementia, and propose a predictive costs model. The expenses analysis was based on (1) the use of emergency rooms and doctor’s appointments, either in public or private institutions; (2) days of hospitalization; (3) medication; (4) social services use; (5) the need for technical support; and (6) the utilization of rehabilitation services. The sample was composed of 72 people, half with dementia and half without. The average annual expense of a patient with dementia was e15,287 thousand, while the cost of a patient without dementia was about e12,289 thousand. The variables “ability to make yourself understood,” “self-performance: getting dressed” and “thyroid disorders” were found to be statistically significant in predicting the expenses’ increase. In nursing homes, in 2012, the costs per patient with dementia were 1, 2 times higher than per patient without dementia.